Constructing Dienes Blocks With Magnetic Cubes – A Preschool Game Named Klickinary: Intriguing Improvement of Number Representation Learning (Constructionism Conference Proceedings, 2025)
The purpose of this approach is to enhance the idea of Dienes multibase arithmetic blocks with even more intriguing elements. In the proposed counting game preschool children are encouraged to construct the Dienes blocks themselves by bundling magnets. First results in the field – on a very small sample – are very promising. The algorithm can be handled even at the age of 3. Correct numbering for base two and other bases is easily reached by almost nonverbal means. Moreover, high intrinsic motivation was observed with the children insisting to play the game again.